Basic Support Of Migrant Workers In Malaysia: A Legal Perspective - Rahim, Rohani Abdul; Tajuddin, Muhammad Afiq Ahmad; Bakar, Kamarudin Abu (Universiti Sains Malaysia, 2016)
Migrant workers are regarded as backbone to the development of Malaysia. As such, the importation of migrant workers in Malaysia is a necessity when the country is facing an acute shortage of labour force in various work sectors such as plantation, manufacturing, construction, agriculture, domestic workers and services. The 11th Malaysian Plan (2016-2020) aim is to reduce dependency and reliance on lowskilled migrant workers especially in labor-intensive activities and to ensure migrant basic support such as basic rights are provided as determine by the existing governing laws. Basic support such as food, clothing, shelter and education are regarded as basic natural human necessities to sustain life. These necessities have been recognized as basic rights for every individual and as a form of human rights that is right to life. Migrant workers upon migrating from their country of origin uphold their civil rights that need to be respected by the receiving countries. Rights to basic support are guaranteed under the Federal Constitution and being the supreme law of the land, it protects everyone who resides in Malaysia, including the migrant workers. This paper discusses on the meaning of basic support in the context of migrant workers; the different forms of basic support made accessible to migrant and local workers and how they were channeled? Finally, to determine the extent of protection accorded by law on the basic support given to the migrant workers.